The application of temporal gating in the measurement of response amplitude operators (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Scale model testing of wave energy converters (WEC) in wave flumes and basins is essential for full scale development. One of the parameters commonly measured is the response amplitude operator (RAO), which represents the response of the WEC to wave excitation.  These are typically measured at discrete frequencies using regular waves.  This approach can be slow, depending on the fidelity and frequency resolution.  An alternative is to use a broadband wave source, however reflections from walls can significantly contaminate the frequency response measurement. In this paper, a rapid method for measuring the RAO is presented using a chirp signal to generate waves in the frequency range of interest to measure the transfer function, and a temporal gating technique (commonly used in experimental acoustics and RF engineering) to remove reflections.  The technique will be demonstrated on numerical data, as well as two scale experiments.